A relação do excesso de peso com o consumo alimentar e os níveis de serotonina - VIEIRA, Brenda Ludmilla Braga (2023)
Objective: To evaluate the relationship of overweight with food consumption and serotonin levels. Methodology: A descriptive, retrospective study was carried out from September 2017 to July 2018, with data from 18 patient records of the Centro de Referencia em Obesidade, of both sexes and age between 24 and 60 years. Patients diagnosed as overweight (BMI 25.0 29.9 kg / m²) and obesity (BMI> 30 kg / m²), according to the WHO (1997), with 24hour recall data, were accepted for this study. R24h) and the serotonin test results from July to August 2016, considering normal levels of 30 to 200 ng / dL. For analysis of the 24hour Reminder, DietSmart Software version 8.5.1 was use, where the values of energy, macronutrients and neutral amino acids were obtain. Results: Of the 18 charts: 8 (44.4%) were female and 10 (55.6%) were male. Of the total, 2 (11.1%) patients were overweight, 4 (22.3%) were grade I, 6 (33.3%) were obese and 6 (33.3%) were obese. Blood levels of serotonin levels showed normal results (30200 ng / dL); however, levels has tended to increase with increasing levels of obesity: in grade I obese patients (76.33 ± 26,48), grade II (105.78 ± 47.16) and grade III (118.68 ± 63.47) and presented a higher level in overweight patients (183.93 ± 12.06), taking into account that this result is only two patients, therefore, a data that should be better investigated. The mean intake of protein (128.3 ± 62.7), lipid (83.6 ± 60.5) and energy (2156.0 ± 779.9) was higher in patients with grade I and carbohydrate obesity (234.0 ± 192.5) higher with grade II obesity. The mean intake of valine (2459.2 ± 1622.3), isoleucine (2386.4 ± 1722.6), phenylalanine (1967.7 ± 1456.2), leucine (3614.1 ± 2496.2) and tryptophan (647.4 ± 284.6) presented higher in patients with grade I obesity and tyrosine (764.4 ± 0) with degree III obesity. Conclusion: Serotonin levels has increased as obesity levels increased and mean intake of macronutrients (protein and lipid), energy and amino acids (valine, isoleucine, phenylalanine, leucine and tryptophan) were higher in obese patients grade I, it was observed that these participants are the lowest level of serotonin, justifying that after meals rich in protein and low in carbohydrate these amino acids compete with tryptophan to cross the hematoencephalic barrier and due to this, lower availability of tryptophan, thus, decreased serotonin production. Therefore, we can verify that the diet is relate to the serum serotonin levels of these participants.